Accessory meningeal artery: an anatomic misnomer. - Vitek, J J (American Journal of Neuroradiology, 1989)
The accessory meningeal artery is misnamed in view of the territory the artery supplies. The name implies that the vessel is an important addition to the middle meningeal artery in supplying the meninges. This is incorrect, because no more than approximately 10% of the blood flow of the accessory meningeal artery reaches the intracranial territory; 90% of the blood is carried to the extracranial structures. After reviewing the anatomy of the accessory meningeal artery we support the notion that the proper name of the vessel should be arteria pterygomeningica, or pterygomeningeal artery.